A Survey on an Effective and Efficient Approach for Low Network Bandwidth Users - R Pujari, Amol; V Patil, Siddheswar (International Journal of Computer Sciences and Engineering, 2015)
The World Wide Web is a huge information repository. It is being used for various purpose such as communication, social networking, business, education and entertainment, the user increasingly demand web content to be delivered without delays. Its popularity is resulting in heavy traffic in the internet which causes long latency as user experience. Potential source of latency are Web servers heavy load, network congestion, low bandwidth and propagation delay. Web caching and Web perfecting are two important techniques used to reduce the noticeable response time. In this paper we have presented survey on recent different web caching and prefeching techniques solutions. We identified and compared their advantages and weaknesses.